1990
DOI: 10.1007/bf02897254
|View full text |Cite
|
Sign up to set email alerts
|

The effect of route of administration and fractionation of dose on the metabolism of ifosfamide

Abstract: The measurement of urinary ifosfamide, isophosphoramide mustard, dechloroethyl ifosfamide and carboxyifosfamide using high-performance thin-layer chromatography with photographic densitometry (TLC-PD) is described. This technique was also used to demonstrate the large inter-individual variation in the ifosfamide metabolic profile of patients receiving the drug as single-agent therapy for non-small-cell lung cancer. In addition, oral administration was shown to result in higher levels of these metabolites in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
2

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…In fact, our results for total urinary excretion of urine metabolites are almost identical to those of Boddy and Idle (1992), who used the same method. An earlier study found only 9% of administered dose in the urine (Lind et al, 1990).…”
Section: Discussionmentioning
confidence: 86%
“…In fact, our results for total urinary excretion of urine metabolites are almost identical to those of Boddy and Idle (1992), who used the same method. An earlier study found only 9% of administered dose in the urine (Lind et al, 1990).…”
Section: Discussionmentioning
confidence: 86%
“…For this study we used a continuous infusion over three days because of a low reported incidence of haemorrhagic cystitis and myelosuppression compared with other schedules (Cerny et al, 1990;Lind et al, 1990). No instances of haemorrhagic cystitis were observed in this study but myelosuppression was common and dose-limiting as expected.…”
Section: Discussionmentioning
confidence: 85%
“…The hepatic metabolism of IF has been extensively studied and occurs in the liver by two major pathways, Fig. 1 [6][7][8][9][10][11]. One pathway involves the 4-hydroxylation of IF and eventually leads to the production of the cytotoxic isophosphoramide mustard [6].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the N-dechloroethylation pathway has been associated with treatment-ending central nervous system (CNS) toxicity [5,[7][8][9]. The N-dechloroethylation pathway is regioselective and enantioselective [10,11] and, as a result, (R)-IF and (S)-IF have distinct efficacy and toxicity profiles.…”
Section: Introductionmentioning
confidence: 99%